Constantine [videorecording (DVD)] - Reeves, Keanu; Weisz, Rachel, 1970-; LaBeouf, Shia, 1986-; Lawrence, Francis (Warner Home Video, 2005)
Supernatural detective John Constantine and policewoman Angela Dodson travel to the world of demons and angels.